Regionalization of national input-output tables: Empirical evidence on the use of the FLQ formula - Julia Kowalewski (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
This paper contributes to the ongoing debate about deriving the value of the exponent when using Flegg's location quotient (FLQ) formula which helps to simulate regional input-output tables. Using a survey-based regional input-output table, the empirical analysis provides evidence of an optimal for the German Federal of State Baden-Wuerttemberg. Furthermore, an extended formula (SFLQ) is introduced allowing for variation in by industry. Finally, this paper demonstrates the advantage of the SFLQ and finds evidence for a close relationship between the spatial concentration of an industry at the national level and its propensity to import goods and services from other regions.
Keywords: 330; regional input-output table; non-survey method; empirical analysis; Regionale Input-Output-Analyse; Input-Output; Deutschland; Baden-Württemberg